Water-Soluble Trichogin GA IV-Derived Peptaibols Protect Tomato Plants From Botrytis cinerea Infection With Limited Impact on Plant Defenses - Baccelli, Ivan; Luti, Simone; Bernardi, Rodolfo; Favaron, Francesco; De Zotti, Marta; Sella, Luca (Frontiers in Plant Science, 2022)
Peptaibols are non-ribosomal linear peptides naturally produced by a wide variety of fungi and represent the largest group of peptaibiotic molecules produced by Trichoderma species. Trichogin GA IV is a 11-residue lipopeptaibol naturally produced by T. longibrachiatum. Peptaibols possess the ability to form pores in lipid membranes or perturb their surface, and have been studied as antibiotics or anticancer drugs in human medicine, or as antimicrobial molecules against plant pathogens. When applied to plants, peptaibols may also elicit defense responses. A major drawback to the exploitation and application of peptaibols in agriculture is their poor water solubility. In a previous study, we designed water-soluble Lys-containing Trichogin GA IV analogs which were able to inhibit the growth of several fungal plant pathogens in vitro. In the present study, we shed light on the mechanism underpinning their efficacy on plants, focusing on six Trichogin GA IV analogs. Our results highlighted peptide hydrophilicity, rather than helix stability, as the major determinant of their activity against B. cinerea infection in tomato leaves. The peptides showed preventive but not curative efficacy against infection, and lack of translaminar activity, with results reproducible on two tomato cultivars, Marmande and Micro-Tom. Reactive oxygen species (ROS) detection analysis in tomato and Arabidopsis, and expression of defense genes in tomato, highlighted a transient and limited impact of the peptides on the plant defense system. The treatment did not result in significant modulation of defense genes or defense priming. The antimicrobial effect thus emerges as the only mechanism behind the plant protection ability exerted by water-soluble Trichogin GA IV analogs, and limited effects on the plant metabolism are expected to occur.